A Review of Suramadu Regional Development Acceleration towards Sustainable Development Concept - Firre An Suprapto; Agus Manshur (Pusbindiklatren Bappenas, 2020)
Based on the Surabaya Madura Regional Development Agency Master Plan 2010-2024, Madura Island has a strategic position as part of the Gerbangkertosusila Urban National Strategy. There is still, however, a development disparity between Madura Island and East Java. This can be seen from the economic performance of Madura Island which is quite low compared to other districts or cities in East Java Province. Madura Human Development Index (HDI) is below the East Java on average, and the percentage of poor people in Madura is the highest in East Java. Therefore, the development of Surabaya-Madura (Suramadu) must be integrated through regional development, such as development of connectivity systems. The research used descriptive analysis to assess the characteristics of a program and to adjust the characteristics with sustainable development theory that consists of three components, namely: environmental, economic, and social developments. These can ultimately be used to sharpen the development target to be achieved in the next 5 (five) years. Data were collected using secondary survey instruments through existing literature studies and policy reviews, such as National Medium-Term Development Plan 2020-2024 and Regional Medium-Term Development Plan of East Java Province.